Arranjo de plantas, características agronômicas e produtividade de soja - Costa, Élide Dalzoto [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The raise in the grain yield of soy bean cultivation has constituted a great challenge, and among the new management practices in study to maximize the productive potential is the use of different spatial plants arrangements. The work had as a objective to evaluate effects of the soy bean plants arrangement of indeterminate growth type on product ion components and grain productivity. The experiment was lead at the ABC Foundation experimental station, in the city of Arapoti, PR, during the agricultural year of 2010/2011. The experimental lineation used was the one with randomized blocks in split po rtions and four repetitions, with the main portion consisted of three spacings between rows (20, 40 and 60 cm) and the subportions by the combination of four plant populations (150, 250, 350 and 450.000 plants ha - 1 ) and two cultivars (BMX PotênciaRR and NA 5909RG). The evaluated characteristics were the leaf closure of plants between sowing rows, the leaf area index, the plant height average, the insertion average height of the first pod, the average number of branches per plant, the average number of pods p er plant, the average number of grains per plant, the average number of grains per pod, the mass of 100 grains and the grains productivity. According to the obtained results, it was concluded that changes in the spatial arrangement of soy bean plants of ind eterminate growth type can positively influence on grains productivity and its components. It was found increased grain productivity with the reducing of spacing between lines, regardless of plants population and cultivar. The raise of soy bean plants popul ation in the sowing row caused reductions in the number of pods per plant, grains per plant and the number of branches; on the other hand, it increased the mass of 100 grains, the plant height average and the insertion average height of the first pod

A elevação do rendimento de grãos na cultura da soja tem - se constituído num grande desafio, e dentre as novas prátic as de manejo em estudo para maximizar o potencial produtiv o está à utilização de diferentes arranjos espaciais de plantas. O trabalho teve como objetivo avaliar efeitos do arranjo de plantas de soja de tip o de crescimento indeterminado sobre os componentes de produção e produtividade de grãos. O experimento foi conduzido na estação experimental da Fundação ABC, no município de Arapoti, PR, durante o ano agrícola de 2010/2011. O delineamento experimental utilizado foi o de blocos ao acaso em parcelas subdivi didas e quatro repetições, com a parcela principal composta de três espaçamentos entre linhas (20, 40 e 60 cm) e as subparcelas pela combinação de quatro populações de plantas (150, 250, 350 e 450 mil plantas ha - 1 ) e duas cultivares (BMX PotênciaRR e NA 59 09RG ). As características avaliadas fora m o fechamento foliar das plantas entre linhas de semeadura, o índice de área foliar, a altura média das plantas, a altura média de inserção da primeira vagem, o número médio de ramificações por planta, o número médi o de vagens por planta, o número médio de grãos por planta, o número médio de grãos por vagem , a massa de 100 grãos e a produtividade de grãos. Em função dos resultados obtidos, concluiu - se que alterações no arranjo espacial de plantas de soja de tipo de c rescimento indeterminado podem influenciar positivamente na produtividade de grãos e seus componentes. Foi verificado aumento da produtividade de grãos com a redução do espaçamento entre linhas, ...
Keywords: Soja - Cultivo; Soja - Espaçamento; Produtividade agrícola; Soybean products